2000
DOI: 10.1111/j.1532-5415.2000.tb02625.x
|View full text |Cite|
|
Sign up to set email alerts
|

Hospitalization in the Program of All‐inclusive Care for the Elderly (PACE): Rates, Concomitants, and Predictors

Abstract: Overall, short-term hospital utilization among PACE participants is low in contrast with that for other older and disabled populations. Participant predictors of hospitalization in PACE are generally consistent with other studies in older clinical and community populations. Both utilization and risk vary considerably across PACE sites, independent of participant-level risk factors, hence suggesting that further investigation is required to study PACE's management of acute illness and hospitalization decisions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 17 publications
6
61
0
1
Order By: Relevance
“…Projects implementing integrated care have taken centre stage as a way to improve quality and efficiency in care for the elderly [3,5]. But adoption of these integrated care models generates implementation problems, and it is difficult to secure the participation of professionals, particularly that of general practition ers (GPs) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Projects implementing integrated care have taken centre stage as a way to improve quality and efficiency in care for the elderly [3,5]. But adoption of these integrated care models generates implementation problems, and it is difficult to secure the participation of professionals, particularly that of general practition ers (GPs) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The unreimbursed costs, as well as the potential regulatory and legal liabilities of caring for sicker residents, are potent disincentives to managing residents with acute changes in status in the NH. [19][20][21][22] Managed care programs such as Evercare and others mitigate these financial incentives and have been shown to reduce hospitalization of NH residents when teams of physicians and NPs or PAs provide more care in the NH, 14,23,24 but the number of NH residents in these programs remains small.…”
mentioning
confidence: 99%
“…Involvement of NPs and PAs in collaboration with primary care physicians has repeatedly been shown to be associated with less hospitalization of NH residents. [12][13][14][23][24][25] Involving these health professionals in care transition interventions in which acute hospitals collaborate with NHs and home health agencies would build upon evolving models, 26,27 but the number of healthcare professionals with special training and interest in geriatrics and long-term care medicine is not increasing rapidly enough to meet this need. 28 Financial incentives to obtain certification in geriatrics or work in NHs, such as loan repayment programs, and the development of a specialty in NH medicine 29 may help in this regard.…”
mentioning
confidence: 99%
“…Other research on homeless veterans noted reductions in emergency department use 24 and emergency department and inpatient use 25 with tailored clinic models, but only after the patients had been enrolled in the program for a least 6 months and in one study 18 months. Studies evaluating the Program of All-Inclusive Care for the Elderly (PACE) models found lower than predicted short term hospital use but with much inter-facility variation suggesting site-specific organization and management practices have an independent effect these findings 26 . Lastly, Pirraglia et al in an analysis of Veterans Administration hospitalization data found that sites with primary care co-located within mental health for patients with serious mental illness had significantly less ambulatory sensitive hospitalizations 27 .…”
Section: Discussionmentioning
confidence: 99%